Dynamic response of functionally graded plates resting on two-parameter-based elastic foundation model using a quasi-3D theory. Issue 4 (4th July 2019) - Adhikari, Balakrishna; Singh, B. N.
Abstract: In this article, an improved quasi 3-D theory, which considers transverse normal strain effect along with inverse tangential variation of in-plane displacements across plate thickness, is employed to encapsulate the response of thick functionally graded plates. The present model satisfies both non-linear variation and zero transverse shear stresses across plate thickness. The governing equations of plate are obtained using Lagrange equation and solved by applying finite element procedure. The adaptability of the proposed theory is handled by considering the impact of various parameters on dynamic response of plate through several illustrations. The present model gives incredible concurrence with accessible literature.